Real Balances, The Exchange Rate, and Indexation: Real Variables in Disinflation - Fischer, Stanley (Quarterly Journal of Economics, 1988)
The paper shows first that real exchange rate appreciation typically reduces, but may increase, the output costs of disinflation. The direct favorable effects of cheaper imports on consumer prices, on the prices of imported inputs, on wage demands, and on the demand for money may be outweighed by the unemployment caused by the trade deficit. Second, the effects of wage indexation on the costs of disinflation are reexamined. Ex ante indexation speeds up disinflation. Ex post indexation, the type observed in practice, automatically increases the real wage at the start of a disinflation and may therefore increase the sacrifice ratio.